Flora of the disrupted habitats in the floodplain landscape of the Oka River and the sources of its formation - Egorova , V. N. (Проблемы ботаники Южной Сибири и Монголии, 2022)
From the second half of the 20th century and up to the present, the floodplain ecosystem has been under high anthropogenic pressure. During this period, various types of disruption appeared in the inner-landscape habitats as a result of human economic activity, which account for more than 50 % of the total area of the Oka River floodplain landscape. This paper conducts a biomorphological and taxonomic analysis of the flora of disrupted inner-landscape habitats, which are grouped into two types. The species composition of flora of disrupted habitats and natural communities of the floodplain during the period 1907-1910 and 1997-2005, which experienced low anthropogenic pressure, were compared. In the flora of inner-landscape disrupted habitats of types I and II, 92.3 % are common species of the flora of all disturbed habitats. It was established that native species play a key role in the formation of flora and vegetation of all the disrupted habitats. The role of adventive species in this process is less significant.